(untitled) (Proceedings of International Conference on Special Education, 2019)
A number of hearing impaired students who are undergoing a special-skilled certificate programme in Politeknik Ibrahim Sultan have difficulties in enhancing their English language skills. A full comprehension and application of selected words or phrases are a challenge for hearing impaired students whose exposure of the language in question is rather restricted. Observations were carried out on two groups of hearing impaired students. Both groups have been exposed to the targeted selected words and phrases. In fact, the groups have also been guided to develop two of the language skills with the application of the targeted selected words and phrases. The hearing impaired students have been drilled to write and read the targeted selected words and phrases. With the comprehension and application of the targeted selected words and phrases laid down to the students, a specially designed language board game is used to test the students’ language skills. The two identified difficulties faced by the students when attempting to apply their language skills during the game are misinterpretation of the targeted selected words / phrases and fragmented sentence structure.